Lepidoptera de Santa Maria e arredores. III. Morphidae e brassolidae - Link, Dionisio; Biezanko, Ceslau M.; Carvalho, Solon; Tarragó, Manoel Fernando S. (Revista do Centro de Ciências Rurais, 2008)
Três espécies de Morphidae e sete espécies de Brassolidae foram coletadas em Santa Maria e regiões próximas. Foram referidos épocas de captura, hábitos de adultos e de larvas e plantas hospedeiras, quando conhecidos.AbstractThree species of Morphidae and seven species of Brassolidae ( Lepidoptera) were found to occur at Santa Maria and neighboring regions. Data were collected on the habits of adults and larvae and host-plants were noted when know.